Climate Change, Fossil-Fuel Pollution, and Children’s Health - Perera, Frederica; Nadeau, Kari (The New England journal of medicine, 2022)
Climate change and air pollution, largely caused by the burning of fossil fuels, pose serious harms to children’s health. Children from communities of color and low-income communities are disproportionately harmed.